Bone mineral density and biochemical parameters of bone metabolism in female patients with systemic lupus erythematosus. Issue 4 (1st April 2000) - Redlich, Kurt; Ziegler, Sophie; Kiener, Hans P; Spitzauer, Susanne; Stohlawetz, Petra; Bernecker, Peter; Kainberger, Franz; Grampp, Stephan; Kudlacek, Stefan; Woloszczuk, Wolfgang; Smolen, Josef S; Pietschmann, Peter
Abstract : OBJECTIVE: To evaluate bone mineral density and biochemical parameters of bone metabolism in ambulatory premenopausal female patients with systemic lupus erythematosus (SLE). METHODS: 30 women who fulfilled the ARA criteria for the classification of SLE were studied. Lumbar and femoral bone mineral density was determined by dual energy x ray absorptiometry. Various laboratory parameters including serum calcium, serum phosphorus, alkaline phosphatase, bone specific isoform of alkaline phophatase, propeptide of type 1 procollagen, deoxypyridinoline excretion, telopeptide of type 1 collagen, serum creatinine, osteocalcin, parathyroid hormone, 25-OH vitamin D, testosterone, progesterone, estradiol, follicle stimulating hormone and luteinotropic hormone were measured. RESULTS: According to the WHO criteria 39% of all patients with SLE studied had normal bone mineral density, 46% had osteopenia and 15% had osteoporosis at the lumbar spine; at the femoral neck 38.5% had normal bone mineral density, 38.5% had osteopenia and 23% suffered from osteoporosis. Significantly lower osteocalcin levels were found in SLE patients. All other bone resorption and formation markers measured were not statistically different, but higher serum albumin corrected calcium and lower phosphorus values were found in the SLE group. Of all sex hormones tested lower testosterone and higher follicle stimulating hormone concentrations were seen in patients with SLE. CONCLUSION: A high incidence was found of osteopenia and osteoporosis in premenopausal patients with SLE. Bone diminution in SLE seems to be attributable, at least in part, to decreased bone formation in SLE patients.